Delivering COBie with ProNIC-compliance and implementation - Hipólito Sousa (2018)
Continuous improvement on information consistency and interoperability are main concerns for some public owners in Portugal. The present research benefits from a large implementation on more than 100 projects where standard procedures, bill of quantities and specifications were used by a large number of agents during design and construction. Facility management is a main concern and rework during handover constitutes a waste of effort. Through the use of COBie it is possible to foster interoperability, extending the integration of processes from design to use. The scope of the research was to observe the ability of ProNIC to deliver COBie drops. The results were beyond the expectations, meaning that ProNIC can provide COBie drops during design and with improvements deliver a more satisfactory drop at the end of construction/during handover, fostering the demands of the industry in terms of efficiency and contributing to the competitiveness.